First M87 Event Horizon Telescope Results. VIII. Magnetic Field Structure near The Event Horizon - The Event Horizon Telescope Collaboration; Kazunori Akiyama; Juan Carlos Algaba; Antxon Alberdi; Walter Alef; Richard Anantua; Keiichi Asada; Rebecca Azulay; Anne-Kathrin Baczko; David Ball; Mislav Baloković; John Barrett; et al. (The Astrophysical Journal Letters)
Event Horizon Telescope (EHT) observations at 230 GHz have now imaged polarized emission around the supermassive black hole in M87 on event-horizon scales. This polarized synchrotron radiation probes the structure of magnetic fields and the plasma properties near the black hole. Here we compare the resolved polarization structure observed by the EHT, along with simultaneous unresolved observations with the Atacama Large Millimeter/submillimeter Array, to expectations from theoretical models. The low fractional linear polarization in the resolved image suggests that the polarization is scrambled on scales smaller than the EHT beam, which we attribute to Faraday rotation internal to the emission region. We estimate the average density n _e ∼ 10 ^4–7 cm ^−3 , magnetic field strength B ∼ 1–30 G, and electron temperature T _e ∼ (1–12) × 10 ^10 K of the radiating plasma in a simple one-zone emission model. We show that the net azimuthal linear polarization pattern may result from organized, poloidal magnetic fields in the emission region. In a quantitative comparison with a large library of simulated polarimetric images from general relativistic magnetohydrodynamic (GRMHD) simulations, we identify a subset of physical models that can explain critical features of the polarimetric EHT observations while producing a relativistic jet of sufficient power. The consistent GRMHD models are all of magnetically arrested accretion disks, where near-horizon magnetic fields are dynamically important. We use the models to infer a mass accretion rate onto the black hole in M87 of (3–20) × 10 ^−4 M _⊙ yr ^−1 .